2010
DOI: 10.5539/apr.v2n1p144
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Anderson-Gruneisen Parameter for NaCl

Abstract: Considering the thermodynamic and thermoelastic properties such as the volume thermal expansion, the thermal expansivity, the isothermal bulk modulus and the Anderson-Gruneisen parameter, we find that the already existed theories presented by other workers are imperfect for NaCl. In the present communication a new expression of temperature dependence of Anderson-Gruneisen has been constructed from room temperature to melting temperature. The results show good agreement with the experimental data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Number of methods have evolved for the determination of density and thermal expansion of solids at high temperature like Archimedean method, pycnometry, dilatometry, electromagnetic levitation, Method of maximal pressure in gas bubble, method of sessile drop, hydrostatic weighing, high temperature electrostatic levitation and gamma ray densitometry. Thermal expansion studies on alkali halides have been reported by several workers using X-ray diffraction [1][2][3], dilatometry [4,5], Fabrey-Perot interference method [6] and by other theoretical models [7][8][9][10][11][12][13][14]. Using γ-ray attenuation technique W. D. Drotning [15] measured thermal expansion of isotropic solid materials at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Number of methods have evolved for the determination of density and thermal expansion of solids at high temperature like Archimedean method, pycnometry, dilatometry, electromagnetic levitation, Method of maximal pressure in gas bubble, method of sessile drop, hydrostatic weighing, high temperature electrostatic levitation and gamma ray densitometry. Thermal expansion studies on alkali halides have been reported by several workers using X-ray diffraction [1][2][3], dilatometry [4,5], Fabrey-Perot interference method [6] and by other theoretical models [7][8][9][10][11][12][13][14]. Using γ-ray attenuation technique W. D. Drotning [15] measured thermal expansion of isotropic solid materials at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, for typical ionic crystals, such as alkali halides, the AG parameter is constant over a wide range of temperatures [14,15]. In the past, some researchers have studied the temperature dependence of the AG parameter [16][17][18][19]. However, concerning ionic conductors, only few studies have been done [20].…”
Section: Introductionmentioning
confidence: 99%
“…Several theories have been proposed in the literature [60]. A good agreement with experimental data is represented by the model proposed in [61], according to which the Grüneisen parameter can be expressed in terms of the temperature as follows:…”
Section: Consequences At Early Timesmentioning
confidence: 83%
“…Here, T 0 is a reference temperature 3 , while b 1 and b 2 are free coefficients obtained by fitting experimental data at different temperatures. The authors in [61] found b 1 = 1.45 × 10 −4 K −1 and b 2 = 5.40 × 10 −7 K −2 . Due to Eq.…”
Section: Consequences At Early Timesmentioning
confidence: 96%